Peran Pendidikan Agama Kristen dalam Meningkatkan Toleransi Beragama Di Kalangan Peserta Didik - Prawono, Yanwar; Kamea, Jeferson (Sekolah Tinggi Agama Kristen Luwuk Banggai, 2024)
The existence of inter-religious conflict in Indonesia shows the need for various approaches to developing religious tolerance, including through the role of Christian Education (CE). This research aims to determine the role that CE can play in developing religious tolerance among students. The method used is literature study. The research results show that CE has an important role in increasing religious tolerance through several ways. First, CE teaches about love which underlies tolerance. Second, CE facilitates the recognition and appreciation of diversity and encourages interfaith dialogue which helps reduce prejudice. Third, the example of CE teachers in showing tolerance is a key factor in creating a tolerant learning environment. In addition, CE helps students overcome stereotypes and prejudice, and apply the values of tolerance in everyday life. With this approach, CE can create a generation capable of living in religious diversity in peace and mutual respect.